2010
DOI: 10.1016/j.archoralbio.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tooth extraction on alveolar bone biomechanics in the miniature pig, Sus scrofa

Abstract: Objective This study investigated the role of occlusion in the development of biomechanical properties of alveolar bone in the miniature pig, Sus scrofa. The hypothesis tested was that the tissues supporting an occluding tooth would show greater stiffness and less strain than that of a non-occluding tooth. Design Maxillary teeth opposing the erupting lower first molar (M1) were extracted on one side. Occlusion developed on the contralateral side. Serially administered fluorochrome labels tracked bone mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…Mandibular torsion or bending during mastication may promote adaptive change of alveolar bone in pigs, and occlusal function may be only a minor factor in determining alveolar bone structure. Although maxillary tooth extractions resulted in greater alveolar strains on occluding side jaws, there were still substantial alveolar strains in the non-occluding side during chewing 12. Masseter muscle activity in conjunction with occlusion of anterior teeth may result in torsional deformation of the mandible during chewing and could account for the strain levels in alveolar bone supporting non-occluding teeth 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandibular torsion or bending during mastication may promote adaptive change of alveolar bone in pigs, and occlusal function may be only a minor factor in determining alveolar bone structure. Although maxillary tooth extractions resulted in greater alveolar strains on occluding side jaws, there were still substantial alveolar strains in the non-occluding side during chewing 12. Masseter muscle activity in conjunction with occlusion of anterior teeth may result in torsional deformation of the mandible during chewing and could account for the strain levels in alveolar bone supporting non-occluding teeth 13.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of tooth extraction surgeries on the masticatory system has been described previously 12. Electromyography was used to track chewing activity before and after tooth extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Based on indirect evidence, however, we reason that a functional overloading at the non-extraction site is less likely. The tooth extracted in this study (dm2) is relatively small (indicated by low strain values in Table 2 compared to those from a molar location (21)) and likely not so functionally critical as to require compensatory overactivity of the non-extraction side. Lack of compensation is supported by the fact that pigs did not favor the non-extraction side during chewing (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…With this value included, the IE-extraction site measurements showed a coefficient of variation of 1.062, and with it excluded, the coefficient of variation was 0.698 (Table 2). Previous studies on bone surface masticatory strain measurements from the pig report coefficients of variation values in a range of 0.2–0.7 (21, 30, 33). In the SE group, strain was nearly identical between the extraction and non-extraction sites (2-sample t-test, p = 0.846) and the coefficient of variation was less than 0.7 at both sites.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation